2012
DOI: 10.1246/cl.2012.1218
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Condensed Monolayer and Multilayer Formation of Hexadecylpyridinium Chloride–Sodium Dodecyl Sulfate Mixed Systems at the Air/Water Interface

Abstract: The adsorption dynamics of mixed adsorbed films of hexadecylpyridinium chloride (HPC) and sodium dodecyl sulfate (SDS) were investigated through external reflection absorption FTIR (ERA FTIR) and surface tension measurements, following two different experimental approaches. In the first approach (case 1), solutions of SDS and HPC, at the desired total concentration and composition, were first introduced into the measurement cell, and then, the measurement was started. In the second approach (case 2), the HPC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Nevertheless, ST itself remains an important thermodynamic measurement. Spectroscopic methods, although not generally effective for determining the surface excess in monolayers, can be useful in the multilayer situation as shown by Takumi et al, 13 who used the IR intensity to measure extra surfactant above a monolayer. Ellipsometry is sensitive to the surface excess and can detect anomalous excesses above a monolayer, 14 but it cannot resolve multilayer structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Nevertheless, ST itself remains an important thermodynamic measurement. Spectroscopic methods, although not generally effective for determining the surface excess in monolayers, can be useful in the multilayer situation as shown by Takumi et al, 13 who used the IR intensity to measure extra surfactant above a monolayer. Ellipsometry is sensitive to the surface excess and can detect anomalous excesses above a monolayer, 14 but it cannot resolve multilayer structure.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The nonionic surfactant with a bulky headgroup (C 12 E 8 or C 12 E 12 ) introduces a steric hindrance which disrupts the complex formation, as originally proposed by Alargova et al 17 Although surface multilayer structures have been reported previously in concentrated surfactant systems, 24−26 in lung surfactants, 27,28 and in polyelectrolyte/surfactant mixtures, 29 there are relatively few observations reported for relatively dilute systems. 22,23,30,31 The surface multilayer structures induced by polyelectrolytes 29 and multivalent counterions 22,23 exhibit extreme and persistent wetting properties on hydrophobic surfaces and offer great potential for applications requiring enhanced adsorption, delivery and retention of benefit agents to interfaces, and in soft or biolubrication.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Surface multilayer formation or surface self-assembly from more concentrated surfactant solutions, in lung surfactants, , layer-by-layer polyelectrolyte deposition , and in polyelectrolyte/surfactant mixtures have been extensively reported. In contrast, reports on surface self-assembly and surface multilayer formation from dilute surfactant solutions, in mixtures, , induced by multivalent counterions or oligoions , are relatively sparse and recent. However their marked and persistant wetting properties, their enhanced adsorption and efficient delivery and retention of different benefit agents (such as perfumes) are potentially attractive for many applications.…”
Section: Introductionmentioning
confidence: 99%